The Safety of Radioiodine Therapy for Women of Reproductive Age - Aisyah Elliyanti (Journal of Midwifery, 2019)
Radioiodine (131I) is  an essential adjuvant treatment after thyroidectomy in patients with differentiated thyroid carcinoma as well as Graves’ disease (hyperthyroidism). Generally 131I is safe, It has some side effects. Infertility is one an important issues for patients who will consider to receive the therapy, especially for woman in reproductive age.  This is reviewed in this paper. Studies reported, in hyperthyroidism and thyroid cancer patients who received  131I therapy, demonstrated no significant radiation effect, some of patients may have experienced short-term reproductive organs disfunction and changes generally resolve. There is no effect of 131I to subsequent pregnancy documented.